Shirohige's Leadership Study in One Piece Anime: Semiotic Approach - Rhapsody Bahyrahmatbrizhar Jazziray; Syahara Dina Amalia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study aims to analyze the construction of Shirohige's leadership representation in the anime One Piece. Specifically, this study aims to identify how this representation is constructed Semiotically, the motives behind its application, and the leadership typology it reflects. This research used a qualitative approach with the main subject was the anime One Piece, focusing on the scenes and interactional dialogues between Shirohige and his crew, particularly in the Marineford Arc and flashback scenes. The data were collected through visual recording and transcription of dialog from selected scenes that depicted Shirohige's leadership. The analysis was conducted systematically by using Peirce's triadic model. The results of the study show that Shirohige's leadership through Icons, Indexes, and Symbols collectively produce the Interpretant of affective loyalty and sacrifice-based authority. The motives of Shirohige's leadership centers on identification as a psychological foundation. Functionality as a survival strategy. Symbolism as an ideological justification for group morality. Shirohige's leadership style is hybrid because it combines elements of Paternalistic, Charismatic, Transformational, and Prophetic leadership, ultimately leading to Kinship-Based Leadership with a focus on moral integrity and compassion. This study is expected to contribute to popular literature studies by having another anime as the subject of Semiotic analysis or by investigating leadership in other kinds of literary works. The findings of this study can also be used as a sample of reference for case study material or teaching material in character education and leadership courses to analyze the construction of moral values and effective leadership models.